What offers solution to the poverty reduction of the Haor people in Bangladesh? Seasonal migration or a new inshore economic livelihood policy - Rabby, Talukder Golam; Alam, Gazi Mahabubul; Fredericks, Leo Jocelyn; Nair, Sulochana; Nurul Azam, Mohammad; Al-Amin, Abul Quasem (Academic Journal, 2011)
Researches from different disciplines are yet to provide a concrete standpoint on causal relationship between poverty and migration. With a market driven attitude, seasonal migration has been increasing dramatically with a hope to reduce the poverty. So far, research has not confirmed if migration helps to reduce poverty or poverty is forced to be migrated. Whatever the fact, it would be realistic that the local community will not migrate if they find better work opportunities with higher productivity for their livings. In this paper, an effort is made to discover the possible ways to make the local community in the Haor area to be productive, ensuring their stay in their homes. A development economic policy guideline is aimed to be provided in order to make the possible ways functional. Along drawing individual and household profile of migrant, a mixed method suggests that some interventions of food stamp, infrastructure facilities and cooperative activities are necessary for in-situ socio-economic development of the Haor people. The outcomes of the study are reliable to apply in underprivileged ecological areas in other developing countries alike.